Anti-coxsackievirus B4 (CV-B4) enhancing activity of serum associated with increased viral load and pathology in mice reinfected with CV-B4. Issue 6 (18th August 2017) - Elmastour, Firas; Jaïdane, Hela; Benkahla, Mehdi; Aguech-Oueslati, Leila; Sane, Famara; Halouani, Aymen; Engelmann, Ilka; Bertin, Antoine; Mokni, Moncef; Gharbi, Jawhar; Aouni, Mahjoub; Alidjinou, Enagnon K.; et al.
ABSTRACT: In previous studies it was shown that inoculation of Swiss albino mice with CV-B4 E2 resulted in the production of serum IgG capable of enhancing the CV-B4 E2 infection of murine spleen cells cultures. To investigate whether such an enhancing activity of serum can play a role in vivo, we decided to study the CV-B4 E2 infection in mice exposed to successive inoculations of virus. In Swiss albino mice infected with CV-B4 E2 at the age of 21 days, anti-CV-B4 E2 neutralizing and enhancing activities of their serum peaked after 55 d. In contrast, mice inoculated at the age of 55 d expressed much lower activities. Despite the neutralizing activity of serum, CV-B4 E2 inoculated a second time to 55 day-old animals spread into the host. At the age of 72 and 89 d the levels of viral RNA and infectious particles were higher in organs of animals exposed to 2 successive infections compared with animals infected once at the age of 21 d or 55 d. In animals with 2 successive inoculations of CV-B4 E2 there was a relationship between the anti-CV-B4 E2 enhancing activity of serum and the level of viral RNA in organs and an enhancement of pathology was observed as displayed by histological analysis of pancreas and hyperglycaemia. Altogether our data strongly suggest that an anti-CV-B4 E2 enhancing activity in the host can play a role in the outcome of a secondary infection with this virus.